Nutritional Enhancement of Polimaize Lines: Integrating Native Mexican Maize Alleles into High-Yield Varieties - Guadalupe Oyoque-Salcedo; Sergio Arias-Martínez; Oscar Giovanni Gutiérrez-Cárdenas; José Luis Montañez-Soto; Ernesto Oregel-Zamudio; Jesús Rubén Torres-García (Agronomy, 2024)
In this study, we evaluated Polimaize lines, named Polimaize, through the integration of alleles from the Native Blue Corn (NBC-JIQ), a local Mexican maize variety indigenous to the northeast region of Michoacán, Mexico, into elite maize lines curated by the International Maize and Wheat Improvement Center (CIMMYT). This crossbreeding aimed to enhance the nutritional profile of maize, particularly in terms of antioxidants and anthocyanins, which are scarce in elite lines. Our results demonstrated a significant increase in these compounds in the Polimaize lines, with variations due to heterosis. Despite these nutritional improvements, some traits showed decreased concentrations compared to parent lines, notably in sucrose and tryptophan, suggesting a potential trade-off. The study also found significant heritability in amino acids and tryptophan, while hexose sugars showed no substantial heritability. The Polimaize variety exhibited high starch content heritability, comparable to elite lines. Field trials confirmed Polimaize’s promising yield and agronomic traits, highlighting its potential for enhancing consumer health and contributing to sustainable agriculture through enriched crop nutritional quality. This project underscores the value of integrating local race alleles into elite lines, offering genetic diversity in maize cultivation.